The interplay of positive and negative emotions to quit unhealthy consumption behaviors: Insights for social marketers. Issue 4 (November 2020) - Fazal-e-Hasan, Syed Muhammad; Ahmadi, Hormoz; Mortimer, Gary; Sekhon, Harjit; Kharouf, Husni; Jebarajakirthy, Charles
Highlights: Examining the interplay of positive and negative emotions in developing intentions to quit smoking. The perceived harm and cost of smoking enhances smokers' perceptions of guilt. Smokers' regret has a positive impact on their guilt of smoking. Smokers' guilt has a positive impact on smokers' hope in quitting smoking. Exercise frequency moderates the relationship between guilt and hope in quitting smoking. Abstract: Prior research has valued the role that consumers' negative emotions play in formulating the strategies and advertising campaigns for quitting unhealthy consumption behaviors. Unhealthy consumption behaviors, such as smoking, are identified as the most important preventable cause of death globally. This study focuses on the interplay of positive and negative emotions in developing consumers' intentions to quit smoking. The study tests a model that positions consumer guilt and regret as antecedents to consumer hope, and intentions to quit smoking as its consequence. Using survey data from 300 consumers (smokers), the findings also suggest a moderating effect of frequency of physical exercise on the guilt–consumer hope relationship. For marketing theorists, the study advances knowledge of how positive and negative emotions interact to develop intentions to quit smoking. For social marketers, our study provides useful insights for investing in anti-consumption strategies and advertising campaigns for unhealthy consumption behaviors. Chinese Abstract: 以往的研究往往重视消费者的负面情绪在制定摆脱不健康消费行为的策略和广告活动中所起的作用.不健康的消费行为, 如吸烟, 被认为是全球最重要的也是原本可预防的死亡原因.本研究主要探讨积极情绪与消极情绪在形成消费者戒烟意向中的相互作用.这项研究测试了一个模型, 该模型将消费者的内疚和后悔定位为消费者希望的前因, 并将戒烟的意图定位为其结果.基于 300 名消费者 (吸烟者) 的调查数据, 研究结果还表明体育锻炼的频率对消费者的负罪感和希望之间的关系有调节作用.对于市场营销理论家来说, 这项研究增进了对积极情绪和消极情绪如何相互作用以形成戒烟意图的认识.对于社会营销人员来说, 我们的研究为制定反消费策略和针对不健康消费行为的广告活动提供了有用的见解.